Translation Procedure Used In Translating Banking Term in Legal Documents of BCA - Istihayyu Buansari; Ahmad Supriatno; Maulani Pangestu (LPPM Universitas Bina Sarana Informatika, 2020)
Abstract - Banking terminology is specialized language which is quite distinct from the translation of general texts. Specialized translation is meant to improve the communication among experts of a domain and to contribute to the distribution of knowledge across language boundaries. In this research the writer tried to use banking document as the corpus in finding banking terminology. The main focus was the translation of banking terminology in Financial Review of Bank Central Asia into Indonesian, translated by Anang Fachruddin, a sworn translator having its official address in Kalibata. This document is selected to be the subject of this thesis corpus, since there is a number of banking terminology found there. Conducted as a descriptive analytical study, this research was aimed at (1) Identifying the procedures applied in translating banking terminology in legal documents, and (2) to find out to what extent that the use of procedure effect the meaning. The writer chooses Peter Newmark theory of translation procedure since it contains more detail information and explanation. From the total number of 98 terminologies occurred in Financial Review of Bank Central Asia, the writer only found ten out of eighteen procedures of Peter Newmark applied in translating banking terminology in legal document. The procedures are; (1) Literal Translation (34.02%), (2) Transference (26.5%), (3) Naturalization (8.1%), (4) Functional Equivalent (3.0%), (5) Descriptive Equivalent (10.2%), (6) Synonym (3.0%), (7) Shift or Transposition (4.0%), (8) Reduction and Expansion (5.1%), (9) Equivalence and Adaptation (1.0%), (10) Couplets (2.0%). Overall, the Indonesian translated version of banking terminologies did not changed the meaning of the source text which is English version. Keywords: Translation, Sworn Translation, Banking, Legal Document. Abstrak: Istilah perbankan merupakan bagian dari bahasa khusus yang bentuknya berbeda dengan nas umum. Penerjemahan khusus bertujuan untuk meningkatkan komunikasi diantara ahli dan berperan serta dalam memberikan pengetahuan melewati batasan bahasa. Dalam penelitian ini penulis berusaha menggunakan dokumen perbankan sebagai korpus penulisan dalam menemukan istilah perbankan. Fokus utamanya adalah penerjemahan istilah perbankan dalam Tinjauan Keuangan Bank Central Asia ke dalam bahasa Indonesia, diterjemahkan oleh Anang Fachruddin, seorang penerjemah tersumpah berkantor di daerah Kalibata. Dokumen ini dipilih menjadi korpus penulisan karena ada banyak istilah perbankan yang ditemukan disana. Dilaksanakan sebagai penelitian Deskriptif Analisis, penelitian ini bertujuan untuk: (1) mengenali prosedur yang dipakai dalam menerjemahkan istilah perbankan dalam dokumen legal dan (2) mencari tahu sampai sejauh mana penggunaan prosedur diatas mempengaruhi makna. Penulis menggunakan teori Peter Newmark mengenai prosedur penerjemahan karena teori tersebut berisikan lebih bnyak informasi dan penjelasan. Dari 98 istilah yang ditemukan dalam Tinjauan Keuangan Bank Central Asia, penulis hanya menemukan sepuluh dari delapan belas prosedur Peter Newmark yang diterapkan dalam menerjemahkan istilah perbankan di dokumen legal. Prosedur tersebut adalah; (1) Literal Translation (34.02%), (2) Transference (26.5%), (3) Naturalization (8.1%), (4) Functional Equivalent (3.0%), (5) Descriptive Equivalent (10.2%), (6) Synonym (3.0%), (7) Shift atau Transposition (4.0%), (8) Reduction dan Expansion (5.1%), (9) Equivalence dan Adaptation (1.0%), (10) Couplets (2.0%). Secara keseluruhan, istilah perbankan yang diterjemahan ke bahasa indonesia tidak merubah makna dari bahasa sumber atau bahasa Inggris. Kata Kunci: Penerjemahan, Penerjemahan Tersumpah, Perbankan, Dokumen Legal